Human papillomavirus type-specific prevalence in the cervical cancer screening population of Czech women - Tachezy, Ruth; Smahelova, Jana; Kaspirkova, Jana; Salakova, Martina (PloS one, 2013)
BACKGROUND: Infection with high-risk human papillomavirus (HPV)types has been recognized as a causal factor for the development of cervical cancer and a number of other malignancies. Today, vaccines against HPV, highly effective in the prevention of persistent infection and precancerous lesions, are available for the routine clinical practice. OBJECTIVES: The data on the prevalence and type-specific HPV distribution in the population of each country are crucial for the surveillance of HPV type-specific prevalence at the onset of vaccination against HPV. METHODS: Women attending a preventive gynecological examination who had no history of abnormal cytological finding and/or surgery for cervical lesions were enrolled. All samples were tested for the presence of HPV by High-Risk Hybrid Capture 2 (HR HC2) and by a modified PCR-reverse line blot assay with broad spectrum primers (BS-RLB). RESULTS: Cervical smears of 1393 women were analyzed. In 6.5% of women, atypical cytological findings were detected. Altogether, 28.3% (394/1393) of women were positive for any HPV type by BS-RLB, 18.2% (254/1393) by HR HC2, and 22.3% (310/1393) by BS-RLB for HR HPV types. In women with atypical findings the prevalence for HR and any HPV types were significantly higher than in women with normal cytological findings. Overall, 36 different HPV types were detected, with HPV 16 being the most prevalent (4.8%). HPV positivity decreased with age; the highest prevalence was 31.5% in the age group 21-25 years. CONCLUSIONS: Our study subjects represent the real screening population. HPV prevalence in this population in the Czech Republic is higher than in other countries of Eastern Europe. Also the spectrum of the most prevalent HPV types differs from those reported by others but HPV 16 is, concordantly, the most prevalent type. Country-specific HPV type-specific prevalences provide baseline information which will enable to measure the impact of HPV vaccination in the future.
Keywords: DNA, Viral; Uterine Cervical Neoplasms; DNA virů; lidé; mladiství; Adult; Middle Aged; Age Distribution; Alphapapillomavirus; Female; vakcinace; Vaccination; Adolescent; Humans; Species Specificity; druhová specificita; Česká republika; lidé středního věku; věkové rozložení; mladý dospělý; Czech Republic; ženské pohlaví; Young Adult; epidemiologické monitorování; nádory děložního čípku; Aged; dospělí; Epidemiological Monitoring; senioři